2017
DOI: 10.1007/s10482-017-0872-0
|View full text |Cite
|
Sign up to set email alerts
|

Studies on lipid A isolated from Phyllobacterium trifolii PETP02T lipopolysaccharide

Abstract: The structure of lipid A from lipopolysaccharide of Phyllobacterium trifolii PETP02T, a nitrogen-fixing symbiotic bacterium, was studied. It was found that the lipid A backbone was composed of two 2,3-diamino-2,3-dideoxy-d-glucose (GlcpN3N) residues connected by a β-(1 → 6) glycosidic linkage, substituted by galacturonic acid (GalpA) at position C-1 and partly decorated by a phosphate residue at C-4′ of the non-reducing GlcpN3N. Both diaminosugars were symmetrically substituted by 3-hydroxy fatty acids (14:0(3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…The transferase encoded by the gene designated as rgtF is responsible for the transfer of Gal p A from the donor dodecyl-P-GalA to lipid A, according to Brown and co-workers [ 11 ]. Similar genes have been identified in R. leguminosarum , M. loti , M. opportunistum , Caulobacter crescentus , Aquifex aeolicus , Azospirillum lipoferum [ 11 ], as well as in at least four strains from Phyllobacterium [ 13 ], and in many bacteria from the class α-proteobacteria, where, in several cases, structural studies have confirmed the presence of α-Gal p A at C-1 of lipid A ([ 14 ], and this work). Among them are also bradyrhizobia [ 15 ], photosynthetic Bradyrhizobium BTAi1 [ 16 ], and Rhodopseudomonas palustris BisA53 [ 17 ].…”
Section: Discussionmentioning
confidence: 60%
“…The transferase encoded by the gene designated as rgtF is responsible for the transfer of Gal p A from the donor dodecyl-P-GalA to lipid A, according to Brown and co-workers [ 11 ]. Similar genes have been identified in R. leguminosarum , M. loti , M. opportunistum , Caulobacter crescentus , Aquifex aeolicus , Azospirillum lipoferum [ 11 ], as well as in at least four strains from Phyllobacterium [ 13 ], and in many bacteria from the class α-proteobacteria, where, in several cases, structural studies have confirmed the presence of α-Gal p A at C-1 of lipid A ([ 14 ], and this work). Among them are also bradyrhizobia [ 15 ], photosynthetic Bradyrhizobium BTAi1 [ 16 ], and Rhodopseudomonas palustris BisA53 [ 17 ].…”
Section: Discussionmentioning
confidence: 60%
“…Stenotrophomonas , Bradyrhizobium , Sphingomonas , and Phyllobacterium bacteria were highly abundant in the MC group with low toxicity but can lead to human infection with severe immunodeficiency. They could all secrete lipopolysaccharides (LPS) except Sphingomonas . LPS is one of the most potent inflammatory chemicals, acting on the Toll-like receptor (TLR-4) to induce the expression of inflammatory genes.…”
Section: Resultsmentioning
confidence: 99%
“…The substitution of only the reducing end of lipid A by α-(1→1)-d-GalpA is also not common among bacteria and has been identified in lipids A from a few representative genera. These include the associative diazotroph Azospirillum lipoferum [23], and some rhizobia: M. huakuii [10], M. loti [11], and P. trifolii [24]. On the other hand, the substitution of exclusively the non-reducing end of lipid A by α-d-GalpA-(1→ at position C-4' is not common either, and has been identified in lipids A from a few representatives of rhizobia (R. etli CE3, R. leguminosarum bvs.…”
Section: Discussionmentioning
confidence: 99%